The extent of lymph node yield in central neck dissection can be affected by preoperative and intraoperative assessment and alter the prognosis of papillary thyroid carcinoma - Hu, Jia‐Qian (Cancer Med, 2019)
BACKGROUND: Lymph node yield (LNY) was implemented in the stratification of papillary thyroid cancer (PTC) patients. The effect of LNY may be related to the extent of surgery. This study aims to identify influencing factors for LNY in central compartment neck dissection (CND). METHODS: Data of 13 712 consecutive PTC patients were analyzed retrospectively. Risk factors for LNY in CND and distribution characteristics of LNY were evaluated. Its relationship with prognosis was studied in another cohort of 136 cases. RESULTS: LNY in therapeutic CND was significantly higher than prophylactic CND (Unilateral: 5.55 ± 3.79 vs 3.41 ± 2.77; Bilateral: 8.90 ± 5.10 vs 6.47 ± 4.17, P < .001). Other independent factors included extranodal extension (ETE), tumor size, and concurrent Hashimoto's thyroiditis. The inconsistency distribution of LNY in bilateral CND was associated with preoperative and intraoperative assessment. Patients with significant difference between major and minor LNY suffered from poorer prognosis (10y‐RFS: 58.3% vs 92.0%; HR = 6.719, 95%, P < .0001). CONCLUSIONS: CND surgical procedure, ETE, and Hashimoto's thyroiditis were independent factors of LNY. Inconsistent distribution of LNY was associated with prognosis of bilateral PTC patients. The impact of preoperative and intraoperative assessment on the actual extent of CND can be used to explain the relationship between LNY and PTC prognosis.